The Paradigm of Intervention Policing in Emergency in the Covid-19 Pandemic - Susatyo Purnomo Condro; Semiarto Aji Purwanto; Chairul Muriman Setyabudi (Budapest International Research and Critics University, 2022)
This article aims to analyze the practice of policing in the emergency situation of the Covid-19 pandemic. In an emergency situation, the practice of policing by emphasizing the paradigm of democratic policing or community policing is not effective and fast enough as a strategy in responding to the Covid-19 pandemic emergency situation. The method used in this study is in the form of literature review, and secondary data. This article concludes that the policing paradigm in overseeing the implementation of policies to control the spread of the covid-19 virus uses an intervention policing paradigm, which is a combination of values or norms-based settings in the community with regulations based on the legitimacy of the police authority. Intervention policing is carried out with interventions in the psychological and social sectors.